2022
DOI: 10.3390/vetsci10010011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Comparisons of Body Weight, Average Daily Gain, and Breast Circumference between Slow-Growing Thai Native Chickens (Pradu Hang dum) Raised On-Site Farm and On-Station

Abstract: To ensure that any new technology developed within an experimental station is appropriate to the community’s needs and compatible with the existing systems, on-site farm research is an important component in examining the effectiveness of agricultural research. The present study examined the growth performance and genetics of Thai native chickens under conditions typically experienced by farmers on smallholder farms (on-site farms) compared with at an experimental unit (on-station). There were 1694 Thai native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Raising crossbred native chickens like those in the 25%TN group will increase the production cycles per year by two times the rearing time of purebred native chickens. However, even though the chickens in the 100%TN (Pure Thai native chicken) group had an average body weight, average daily gain, and breast circumference that were the lowest, their BW8 was better than other Thai native chicken breeds, such as Lueng Hang Kao Kabinburi ( 49 ) at 642.08 g at 8 weeks of age, and Pradu Hang dum ( 1 ) at 808.01 g at 8 weeks of age. Importantly, this study demonstrates that the genetic improvement of growth traits is more accurate and better than those studied in other Thai native chicken breeds.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Raising crossbred native chickens like those in the 25%TN group will increase the production cycles per year by two times the rearing time of purebred native chickens. However, even though the chickens in the 100%TN (Pure Thai native chicken) group had an average body weight, average daily gain, and breast circumference that were the lowest, their BW8 was better than other Thai native chicken breeds, such as Lueng Hang Kao Kabinburi ( 49 ) at 642.08 g at 8 weeks of age, and Pradu Hang dum ( 1 ) at 808.01 g at 8 weeks of age. Importantly, this study demonstrates that the genetic improvement of growth traits is more accurate and better than those studied in other Thai native chicken breeds.…”
Section: Discussionmentioning
confidence: 97%
“…Growth characteristics are one of the most economically important traits and have been continuously improved genetically in both commercial strains and native chickens ( 1–3 ) to produce more food for the world’s population, which is growing steadily ( 4 , 5 ). While fast-growing chickens allow farmers to speed up production cycles, the other effect is an increase in undesirable bioactive compounds in the meat, especially increased accumulation of purine content and uric acid levels in meat and organs ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the artificial insemination (AI) procedure has become more familiar to Thai farmers. However, a study showed that rooster fertility on the farm under field conditions was lower than that under experimental conditions [6]. One important concern is that local farmers have no practical method for mating management.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, one breed of Thai native chickens, Pradu Hang Dum (PD; Figure 1 ), is raised in backyard farms in rural households, mainly for home consumption [ 1 ]. Distinct features of its meat, in terms of nutrients (higher protein and nutritional components, lower fat), textures, and flavor, make it superior to commercial broiler meat and now widely consumed [ 2 , 3 ]. Consequently, semicommercial-scale production of this breed is gradually increasing to meet the extensive demands for poultry.…”
Section: Introductionmentioning
confidence: 99%